The Impact of Project-Based Learning Model on Students' Outcomes in Electrical Equipment Repair Subject at SMK Negeri 10 Luwu - Firdaus, Firdaus; Alya Rasta, Ilma; Ashari, Hilda; Triantini, Dewi (Jurnal Pendidikan dan Profesi Keguruan, 2025)
​The efficacy of the Project-Based Learning (PjBL) model in enhancing student learning outcomes in the Electrical Equipment Repair subject at SMK Negeri 10 Luwu was evaluated in this study. A quasi-experimental, nonequivalent control group design was employed, with an experimental group (n=13) exposed to PjBL using heater repair projects and a control group (n=12) receiving conventional instructions. The independent variable was the application of the PjBL model, and student learning outcomes served as the dependent variable. Learning outcomes were assessed via pre- and post-tests supplemented by observations, questionnaires, and documentation. Data were analyzed using a paired sample t-test in SPSS version 26. The results indicated a significant positive influence of the PjBL model on student learning outcomes. The experimental group's average pre-test score of 28.77 significantly increased to 81.31 in the post-test, compared to the control group's increase from 26.33 to 51.00. The paired sample t-test yielded a significance value of (<0.05), confirming a statistically significant effect. Furthermore, students demonstrated a highly positive response to PjBL implementation, with 93% providing favorable feedback. These findings suggest that the PjBL model is an effective pedagogical approach for enhancing student achievement in vocational electrical equipment repairs.​